Design of robotic arm controller based on Internet of Things (IoT) - Ishak, Mohamad Khairi; Roslan, Muhammad Izzat; Ishak, Khairol Anuar (Universiti Teknikal Malaysia Melaka, 2018)
This paper presents the process of developing a controller for a robotic arm that is built through the Internet of Things (IoT).The direction of the robotic arm can be monitored and controlled using internet facilities. The Raspberry Pi board is utilized in this project for the robotic arm controller as well as the web server system.The robotic arm comprises four servo motors and each of the servo motors is assigned with a single pulse width modulation (PWM) output that can be individually controlled.The controller system is implemented on Raspberry Pi board using Python 2.7 programming language.Node-Red is used as a web server in this project to communicate with the web browser through TCP/HTTP.Hence, this allows the user to access the web browser using computer or smartphones.In addition, it enables the monitoring and controlling of the robotic arm direction as well as performing pick and place task similar to the manufacturing industry.The results of this study are verified through practical test implementation.